Maternal Satisfaction with Antenatal Care and Associated Factors among Pregnant Women in Hossana Town - Kebede, Dagmawit Birhanu; Belachew, Yeshitila Belay; Selbana, Desta Workneh; Gizaw, Admasu Belay (International Journal of Reproductive Medicine, 2020)
Background. A woman’s satisfaction with antenatal care service has immediate and long-term impacts on maternal and her baby’s health. It also ensures further use of service. However, it is not well studied in Ethiopia in general and at the southern region in particular. Objective. The main objective of this study is to assess the level of a maternal satisfaction with antenatal care services and associated factors. Methods. An institution-based cross-sectional study that involves both quantitative and qualitative methods of data collection was employed. A systematic sampling technique was used to obtain study participants, and quantitative data were collected using an interviewer-administered questionnaire. For qualitative data, Focus Group Discussions were done among clients that have a repeated visit by taking educational status as homogeneity criteria. EpiData version 3.1 and SPSS version 21 were used for analysis. Descriptive statistics, bivariate and multivariable logistic regression analyses were employed to describe and identify factors associated with maternal satisfaction on antenatal care. The qualitative data were analyzed thematically and manually. Results. Overall, 74% of mothers were satisfied with antenatal care services rendered in public health institutions of Hossana town. Most of the respondents were satisfied with privacy, cleanness, physical facility, and approaches of care. Age, educational status, privacy, cleanness, distance, and respect were significantly associated with a client’s satisfaction. Conclusion. Three-fourths of the respondents were satisfied with the service. Age, education, living distance, maintenance of privacy, cleanness of the facility, and respect from providers were the significant predictors of the satisfaction level.